Comparison of Mean Arterial Pressure (MAP) Values in Elderly Patients Undergoing Transurethral Resection of the Prostate (TURP) with Regional Anesthesia at Banjarnegara Islamic Hospital in 2023. - Fhadilah Putri Syiva Alifa; Martyarini Budi Setyawati; Wilis Sukmaningtyas; Awal Tunis Yantoro (Viva Medika, 2023)
Basic Health Research (2017) stated that around 50% of men aged 50 years in Indonesia suffered from BPH (Benign Prostate Hyperplasia). One of the treatments for BPH is TURP (Transurethral Resection of the Prostate) using spinal anesthesia. A high degree of blockade (≥ T5) and elderly are the two main factors of complication causing changes in MAP (Mean Arterial Pressure) values ​​after spinal anesthesia, which is about 15.3 to 33%. MAP monitoring is very important because MAP describes the status of cerebral perfusion. The research purpose was to determine the comparison of MAP in each age group of the elderly undergoing TURP at Bajarnegara Islamic Hospital. The researcher applied a comparative analytic method with cross sectional approach. The research was conducted in March 2023 with 31 respondents. The samples were taken by using convenience sampling technique. The independent sample t test results showed (p = 0,870). Therefore, there were no significant differences of MAP in each age group of the elderly undergoing TURP at Bajarnegara Islamic Hospital.